Boosting EFL Students’ Paraphrasing Skills Through E-Paraphrasing Tools: A Meta-Analysis Study - Alyami, Naji; Alzubi, Ali Abbas Falah (European Journal of Social Science Education and Research, 2026)
E-paraphrasing tools have a measurable influence on English as a Foreign Language (EFL) learners’ paraphrasing skills. This study employed a meta-analysis to evaluate the impact of such tools on writing- and reading-related outcomes in EFL contexts. The analysis was conducted separately for two study types: (1) two-group experimental designs comparing learners using online tools with control groups and (2) one-group pre-post designs measuring improvement within the same learners after tool use. The results from the two-group analysis demonstrated that learners using e-paraphrasing tools were more than twice as likely to achieve stronger writing outcomes than those in the control groups were. The one-group pre-post analysis revealed a larger pooled effect after excluding an extreme outlier, although substantial heterogeneity suggests variability in the strength of effects across studies. The findings indicate that proficiency level and gender exert minimal influence on outcomes, whereas specific paraphrasing skills, particularly active-to-passive transformations, show significant gains. Synthesizing evidence across designs, the study concludes that AI-assisted paraphrasing tools such as QuillBot, Wordtune, and ChatGPT have a robust and positive effect on EFL learners’ writing proficiency.